Sport finance / Gil Fried, Timothy D. DeSchriver, Michael Mondello. - Fried, Gil, 1965- author (Champaign, IL : Human Kinetics, 2024.)
"Sport Finance guides students through the finance process, linking financial principles to real-world sport finance strategies. It offers a broad overview, helping readers grasp the factors behind the financial success or failure of entities in the sports industry. The book covers essential skills like budget comprehension, asset and liability management, income and expense understanding, and basic money management. It delves into practical topics such as revenue growth, expense reduction, budget development, financial statement analysis, obtaining funding, cash management, and creating a financial strategy. Additionally, industry spotlights and case studies are incorporated to enhance comprehension"-- $c Provided by publisher.
Includes bibliographical references and index.
Keywords: Sports Finance; Sports administration; SPORTS & RECREATION / Business Aspects